PENGARUH PENGETAHUAN PAJAK, SELF ASSESSMENT SYSTEM, PENERAPAN E-FILING, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK YANG MELAKUKAN PEKERJAAN BEBAS - Sandria, Ahmad Maulana; Farina, Khoirina (Universitas Trilogi, 2023)
The study aimed to investigate and analyze how much influence tax knowledge, self-assessment system, application of e-filing, and tax sanctions have on taxpayer compliance of independent workers. The approach used in this research is the quantitative method. Individual taxpayers who carry out independent work at PT BRI Life Insurance, KS Tubun branch as the research population. used as the sampling method used was purposive sampling. The number of selected samples was 72 respondents. The results of this study indicate that taxpayer compliance is influenced by the tax sanction variable.Keywords: Tax Knowledge; Self Assessment System; E-Filling; Tax Sanctions